Refleksi Pembangunan Pendidikan di Indonesia Menyongsong Era Global dan Pasar Bebas - Sunu Priyawan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
High competence and high competitive advantage are required for individuals of any nation or country to survive in this global era. National education system plays a very important role in building up such individuals. This article presents a critical analysis of the Indonesian Education system facing this global and free-trade era. It suggests that the education system focus on educational programs resulting in individuals who can actively take part in the world.